2018
DOI: 10.1371/journal.pntd.0006915
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of clinical Burkholderia pseudomallei isolates from southwestern coastal region of India, using multi-locus sequence typing

Abstract: BackgroundThe Gram-negative soil dwelling bacterium Burkholderia pseudomallei is the etiological agent of melioidosis. The disease is endemic in most parts of Southeast Asia and northern Australia. Over last few years, there has been an increase in number of melioidosis cases from India; however the disease epidemiology is less clearly understood. Multi-locus sequence typing (MLST) is a powerful genotypic method used to characterize the genetic diversity of B. Pseudomallei both within and across the geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Our MLST and phylogenetic analysis demonstrated that B. pseudomallei from Myanmar are genetically diverse and heterogenous, with nine STs identified amongst only sixteen isolates. This finding is consistent with the high levels of genetic and ST diversity in B. pseudomallei from neighbouring countries including India 32 , China 33 and Thailand 34 and in the ancient B. pseudomallei population from the Northern Territory of Australia 35 , 36 . Five of the Myanmar STs had not been previously identified, with four being environmental isolates.…”
Section: Discussionsupporting
confidence: 86%
“…Our MLST and phylogenetic analysis demonstrated that B. pseudomallei from Myanmar are genetically diverse and heterogenous, with nine STs identified amongst only sixteen isolates. This finding is consistent with the high levels of genetic and ST diversity in B. pseudomallei from neighbouring countries including India 32 , China 33 and Thailand 34 and in the ancient B. pseudomallei population from the Northern Territory of Australia 35 , 36 . Five of the Myanmar STs had not been previously identified, with four being environmental isolates.…”
Section: Discussionsupporting
confidence: 86%
“…This uncertainty in the true number of cases and fatalities attributed to melioidosis in Malaysia is related to the lack of awareness of the disease among primary healthcare professionals and the general public. As such, a country-wide survey of B. pseudomallei isolated from melioidosis patients using molecular methods such as sequence typing will be useful to assess the population structure of the organism locally as well as in relation to the worldwide B. pseudomallei population [13,14]. On a broader scope, molecular epidemiology of B. pseudomallei will also provide PLOS NEGLECTED TROPICAL DISEASES insights into the biogeography and factors that influence the distribution of the organism within a particular ecology where such knowledge can assist in public health management during outbreaks [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…pseudomallei isolated from melioidosis patients using molecular methods such as sequence typing will be useful to assess the population structure of the organism locally as well as in relation to the worldwide B . pseudomallei population [ 13 , 14 ]. On a broader scope, molecular epidemiology of B .…”
Section: Introductionmentioning
confidence: 99%
“…We conducted multilocus sequence typing as described previously ( 5 ). This isolate belongs to sequence type (ST) 550, corresponding with isolates previously documented in Vietnam in 2005 ( 6 ). The patient in this study had never been to Vietnam, but Guangxi Province borders that country.…”
mentioning
confidence: 73%
“…We constructed a phylogenetic tree with 1,000 bootstrap replicates using the unweighted pair group method with arithmetic averages in MEGA X software ( https://www.megasoftware.net ). This tree included isolates from other countries in Asia downloaded from PubMLST ( https://pubmlst.org ); the isolate in this study was most closely related to ST175 from Thailand ( Appendix Figure 2) ( 6 ).…”
mentioning
confidence: 99%